Smart city development, the cooperation between the Ministry of Interior and the city Monor: Interview with Miklós Dukai (Academic Journal of Internal Affairs, 2019)
Smart City developments mean an entirety of innovative solutions which make living in the city more liveable, more comfortable and more economic. These developments aim the realisation of complex integrated systems which intend firstly the development of effectiveness and competitiveness of the economy including among others the development of built surroundings, of an integrated traffic control system and of information technologies and further the dissemination of the process results in the widest possible circle. But what does it all mean in the practice, we asked Miklós Durai, deputy secretary of state for self-government in the Ministry of Interior, who was interviewed by Zsuzsanna Hornyik.
Keywords: interview; smart city development; Ministry of Interior; self-government